2016
DOI: 10.1371/journal.pone.0150692
|View full text |Cite
|
Sign up to set email alerts
|

Construction of High-Density Linkage Maps of Populus deltoides × P. simonii Using Restriction-Site Associated DNA Sequencing

Abstract: Although numerous linkage maps have been constructed in the genus Populus, they are typically sparse and thus have limited applications due to low throughput of traditional molecular markers. Restriction-site associated DNA sequencing (RADSeq) technology allows us to identify a large number of single nucleotide polymorphisms (SNP) across genomes of many individuals in a fast and cost-effective way, and makes it possible to construct high-density genetic linkage maps. We performed RADSeq for 299 progeny and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 49 publications
4
71
1
Order By: Relevance
“…Even with the aid of a good framework map and using only those SNPs remaining after application of the premapping filters, we found that map inflation was best minimized using the strict criterion of 5% missing data, a lower value than the 10–25% typically reported for genetic maps constructed with RRS technologies [3, 31, 73, 74]. Improvements in sequencing technologies and methods of library construction could address the problem of missing data, as long as the calling accuracy (the number of times a variant is detected when it is present) is part of the quality control process.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the aid of a good framework map and using only those SNPs remaining after application of the premapping filters, we found that map inflation was best minimized using the strict criterion of 5% missing data, a lower value than the 10–25% typically reported for genetic maps constructed with RRS technologies [3, 31, 73, 74]. Improvements in sequencing technologies and methods of library construction could address the problem of missing data, as long as the calling accuracy (the number of times a variant is detected when it is present) is part of the quality control process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our framework genetic maps are similar in size to the ca. 4200 cM and 3800 cM maps presented by Tong et al (2016) for the more distantly related species…”
Section: P Tremula Linkage Mapsmentioning
confidence: 99%
“…Populus deltoides and Populus simonii, respectively. The large size of these maps led Tong et al (2016) to suggest that their maps were suffering from inflation due to the difficulty of properly ordering a large number of markers within a linkage group. While we likely also suffer from such size inflation, these issues appear to be less severe in our P. tremula parental maps, which contain between 8-14 times the number of markers used in the P. deltoides (1601) and P. simonii (940) maps and yet yield linkage maps of similar size.…”
Section: P Tremula Linkage Mapsmentioning
confidence: 99%
See 2 more Smart Citations